X-linked retinoschisis in three females from the same family: A phenotype-genotype correlation (2005)
Purpose: To describe the clinical findings and outcome for three homozygous females affected with X-linked retinoschisis (XLRS) in a large Colombian family with 26 affected males. Methods: Retrospective review of charts for females from a family with XLRS who underwent complete ophthalmologic examinations, ancillary tests, clinical genetic evaluation, and molecular studies. Results: Three female patients (6 eyes) with clinical findings of XLRS were identified. The patients' ages ranged from 10 to 37 years. Initial visual acuity was equal to or worse than 20/50 in 4 eyes (66%) of 2 patients. Four eyes (66%) were hyperopic. Intraocular pressure was normal in all eyes. Three eyes (50%) had cataracts, and vitreous veils were present in 3 (50%). The optic disk was pale in 6 eyes (100%). Foveal schisis was present in 6 eyes (100%). Peripheral retinal schisis was present in five eyes. A silvery gloss or tapetal-like retinal reflex or sheen was observed in 6 eyes (100%), and dendritic lines were found in 2 (33%). One eye had a retinal break, and one had a retinal detachment. Two eyes underwent cataract extraction; one patient underwent bilateral cryotherapy, one, laser treatment, and one, scleral buckling. Final visual acuity was 20/50 to 20/100 in 2 eyes and 20/200 to 20/400 in 4. Follow-up ranged from 7 to 22 years. Molecular analysis showed that all three female patients were homozygous for the allele 639delG of (on) the XRLS1 gene. Conclusions: Compared with their affected male relatives, three females from a family with XLRS had similar ocular findings and a more severe course of disease. These findings are explained by the fact that these patients were homozygous for a mutation in the XLRS1 gene.